Soil carbon dioxide emissions in a sorghum field: Row position and growth stage effects. Issue 1 (7th February 2021) - Kuang, Xianyan; Xiao, Rong; Xiao, Xinhua; Yuan, Qunying; Sauer, Thomas; Davis, Dedrick
Abstract: Soil carbon dioxide emission (SCE) is known to be impacted by multiple factors including sources of respiration, environmental factors, and crop and soil management practices, yet few reports exist on how crop row position and growth stage affect SCE in sorghum [ Sorghum bicolor (L.) Moench] fields. The objective of this study was to examine the effects of row position and growth stage on SCE dynamics in a field under grain and sweet sorghum production in northern Alabama. Soil CO2 emissions were measured weekly during the growth period using a closed soil CO2 survey chamber system. The results showed that SCEs increased steadily from approximately 4 μmol CO2  m –2  s –1 during the vegetative stage and reached maximum values of approximately about 5 μmol CO2  m –2  s –1 and 6 μmol CO2  m –2  s –1 for grain sorghum and sweet sorghum, respectively. Soil CO2 emissions then decreased to approximately 2 μmol CO2  m –2  s –1 at the maturity and post‐maturity periods for both sorghum types. Significant differences in SCE were observed between row positions. Soil CO2 emissions at the row (R) positions were 19% greater than at interrow (I) positions during the entire growing season under grain sorghum production. Significant difference occurred only during the vegetative stage (SCE at R was 9% greater than at I position) under sweet sorghum production. Additionally, a significantly greater response of SCE to soil temperature ( T s) during the vegetative stage was observed under sweet sorghum production but not grain sorghum production. This study provides evidence that SCE is affected by row position, growth stage, and crop type and suggests that crop row position and growth stage should be taken into consideration for SCE estimation.